Les grandes guerres du XXe siècle dans No pasarán le jeu de Christian Lehmann : écrire et réécrire l’histoire pour les adolescents, du roman à la bande dessinée - Eléonore Hamaide-Jager (Amnis)
Using videogames as a means to tackle the major global conflicts of the twentieth century, Lehmann's trilogy No pasaran, le jeu, Andreas le retour and No pasaran, endgame immediately wins over its teenage readership through its immersive dimension. The fantastic mode allows the characters both to feel rooted in their own time and to viscerally experience the violence, responsibility and doubt inherent to the making of vital decisions concerning humanity's future, especially as their accurate knowledge of past events is a gift protagonists seldom have. The trilogy goes beyond the literary characteristics of the young adult historical novel by bringing the characters to face history and its effects on the present period, which is the same as the readers’. Rather than a mere adaptation, the graphic novel is a rewriting, in which the reading is made more complex by the shortening and reshaping of the overall structure. This version provides a graphic account of the characters’feelings: it successfully conveys the stunning shock the teenagers experience in the face of the events narrated, whereas the novel tends to rely on argumentation and detachment. Arguably neither of the two versions seems up to the task of offering a factual account of wars that have shaped the geopolitics of the 21st century. However, they make it possible for one to feel closer to individuals belonging to family, social and political history; and they succeed in confronting readers with the characters’choices in these double-layered novels, in order to finally make them embrace humanist values and to encourage them to become committed citizens.